2014
DOI: 10.1177/1470320314539829
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between polymorphism of angiotensin-converting enzyme gene insertion/deletion and risk of hepatocellular carcinoma in a Chinese Dai population

Abstract: The DD genotypes of ACE I/D polymorphism might contribute to the prediction of HCC risk in a Chinese Dai population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…In a Chinese population, Yuan et al (2013) demonstrated the ACE gene D allele frequency in patients with HCC to be lower than in healthy controls. Zha et al (2014) also conducted a study on HCC patients, and contrary to the findings reported by Yuan et al (2013), found D allele frequencies to be higher in HCC patients than in the control subjects.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…In a Chinese population, Yuan et al (2013) demonstrated the ACE gene D allele frequency in patients with HCC to be lower than in healthy controls. Zha et al (2014) also conducted a study on HCC patients, and contrary to the findings reported by Yuan et al (2013), found D allele frequencies to be higher in HCC patients than in the control subjects.…”
Section: Discussionmentioning
confidence: 77%
“…Fabris et al (2009), on the other hand, suggested a relationship between gender and ACE gene I/D polymorphism: ACE I/I homozygote women had liver fibrosis scores five times higher than ACE D/D homozygote and ACE I/D heterozygote women. The DD genotype has furthermore been found to be significantly associated with hepatocellular carcinoma (HCC) risk; however, results in this area have been somewhat conflicting: Yuan (2013) found D allele frequencies to be lower in HCC patients than in controls, whereas Zha (2014) found D allele frequencies of HCC patients to be higher than those of controls. The studies carried out to investigate the relationship between ACE gene I/D polymorphism and/or serum ACE levels with liver fibrosis between the years of 2000 and 2015 have yielded conflicting conclusions, which could be attrinuted to the small sample sizes used (Table 1).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…[9][10][11][12][16][17][18][19][20][21][22][23][24][25][26][27] The publication year was from 2001 16 to 2014. 27 …”
Section: Study Descriptionsmentioning
confidence: 99%
“…3 The angiotensin-converting enzyme (ACE) insertion/ deletion (I/D) gene polymorphism is a 287-bp sequence of DNA in the intron 16 of the ACE gene, and the ACE gene includes either an insertion (I) allele or a deletion (D) allele that form three possible genotypes: II, ID or DD. 4,5 ACE, directly involved in the process of cell proliferation, differentiation, apoptosis and angiogenesis, 6 can convert angiotensin I into angiotensin II, and angiotensin II is the main effector molecule of the renin-angiotensin system, is pleiotropic, and is a mediator of the development and progression of diseases. 7 The ACE I/D gene polymorphism, correlating with circulating ACE concentration, might be implicated in the etiology of sepsis and has been investigated in some epidemiologic studies.…”
Section: Introductionmentioning
confidence: 99%